Challenges and Opportunities for Corporate Human Resource Management in the Context of Artificial Intelligence - Han, Limin (International Journal of Global Economics and Management, 2024)
With the continuous development and maturity of Internet technology, big data and artificial intelligence have gradually become the new products of the 21st century, and their applications are expanding while promoting the development of science and technology. As artificial intelligence has the advantages of fast, accurate and convenient, its application in the field of enterprise human resource management has brought a new working mode for enterprise human resource management and put forward higher requirements for enterprise human resource managers. On this basis, this paper gives an overview of the development and application of artificial intelligence, discusses the specific application of artificial intelligence in enterprise human resource management, focuses on the challenges and opportunities faced by enterprise human resource management in the context of artificial intelligence, and aims to bring technical support to relevant departments.